2020
DOI: 10.1111/jbg.12496
|View full text |Cite
|
Sign up to set email alerts
|

Weighted single‐step genome‐wide association study and pathway analyses for feed efficiency traits in Nellore cattle

Abstract: The aim was to conduct a weighted single‐step genome‐wide association study to detect genomic regions and putative candidate genes related to residual feed intake, dry matter intake, feed efficiency (FE), feed conversion ratio, residual body weight gain, residual intake and weight gain in Nellore cattle. Several protein‐coding genes were identified within the genomic regions that explain more than 0.5% of the additive genetic variance for these traits. These genes were associated with insulin, leptin, glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 103 publications
3
23
0
Order By: Relevance
“…Glucagon reduces glucose utilisation in adipose tissue, stimulates lipolysis and increases gluconeogenesis. This pathway was also highlighted in Nellore cattle [ 53 ] and the ADCY2 gene was identified in both our study and [ 53 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Glucagon reduces glucose utilisation in adipose tissue, stimulates lipolysis and increases gluconeogenesis. This pathway was also highlighted in Nellore cattle [ 53 ] and the ADCY2 gene was identified in both our study and [ 53 ].…”
Section: Discussionsupporting
confidence: 79%
“…Linked to this protease, the thrombin signalling pathway was also enriched in a study that performed Ingenuity Pathway Analysis [ 37 ]. Moreover, the thrombin receptor signalling pathway was reported in [ 53 ] and two of the genes, F2RL2 and IQGAP2 , detected in [ 53 ], were found in our study. Both the RG and FE networks also enriched several processes related to the vascular system, such as renin secretion, hematopoietic progenitor cell differentiation, smoothened signalling pathway and platelet activation (see Fig.…”
Section: Discussionsupporting
confidence: 73%
“…For the direct effect of weaning weight, associations were mostly shared across S3.2); KCNIP4 and SLIT2 on BTA6 [17,129]; FBXO32 and ATAD2 on BTA14 [130,131]; METTL15 on BTA15 [132]). In all 3 regions, QTL enrichment analyses identified known large-effect growth QTL including those near ARRDC3, ERGIC1 and BNIP1 ( [133,134]; Table S3.2).…”
Section: Single-step Gwasmentioning
confidence: 99%
“…We also unravel the metabolic pathways related to FE in Nellore cattle showing an increased bacterial load in low feed efficient animals which is in part responsible for the hepatic lesions and inflammation in these animals [16]. Previously, some QTL's for feed efficiency in Nellore beef cattle were found by conventional GWAS [17][18][19][20][21], however only attempts to find causal variants were done.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship matrix used in the analyses was calculated based on pedigree information from 19,507 animals, provided by the Nelore Brazil Breeding Program, coordinated by the National Association of Breeders and Researchers. More information regarding the set of animals used in this study can be found elsewhere[18].3.2.6.2. Genomic informationPhenotypic and genotypic records from the Nelore Brazil breeding program coordinated by the National Association of Farmers and Researchers (Associação Nacional de Criadores e Pesquisadores -ANCP, Ribeirão Preto-SP, Brazil) were used for this study.…”
mentioning
confidence: 99%